A new vision of innovation management: towards an integrated paradigm. (28th August 2006) - Lan, Ping
This paper proposes a model for revealing the shift of an innovation paradigm. It argues the following: that the shift of the basic innovation structure from dichotomous divisions to a unified consolidation has not been identified and addressed; that the shift of innovation outlets from physical to digital plays a key role in changing innovation practices; that the traditional discrete innovation paradigm is being replaced by an integrated paradigm, which is more accommodative in dealing with burgeoning innovation activities.